1980
DOI: 10.1002/pssb.2220990114
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Electronic Excitations in Pure Sodium Silicate Glasses

Abstract: Electronic structure in high-purity sodium silicate glasses is studied. The spectral dependence of the relative quantum yield of the external and internal photoemission, the luminescence excitation spectra, the luminescence decay, and the polarization degree of the luminescence are measured.The luminescence band at 3.4 eV is created by the intrinsic anisotropic luminescence centre labelled L, whose absorption causes the fundamental absorption tail of high-purity silicate glasses, where the localized elementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 6 publications
3
18
0
Order By: Relevance
“…The specific feature of the third band observed in the pulsed cathodoluminescence spectra of the two-alkali silicate glasses upon excitation with a pulsed electron beam (see attributed to the L 2 center, has not been revealed in the steady-state photoluminescence spectra [2,18,[26][27][28][29]. It can be assumed that the possibility of observing the third band in the spectra is associated with the high sensitivity of the pulsed cathodoluminescence method, which exceeds the sensitivity of the photoluminescence method by several orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…The specific feature of the third band observed in the pulsed cathodoluminescence spectra of the two-alkali silicate glasses upon excitation with a pulsed electron beam (see attributed to the L 2 center, has not been revealed in the steady-state photoluminescence spectra [2,18,[26][27][28][29]. It can be assumed that the possibility of observing the third band in the spectra is associated with the high sensitivity of the pulsed cathodoluminescence method, which exceeds the sensitivity of the photoluminescence method by several orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…An area of blue luminescence can be seen in the glass bulk. This blue luminescence in silicate glasses results from recombination of intrinsic electron and hole centers produced by glass matrix ionization [12,13]. It was found that the area emitting this luminescence corresponds to the area of refractive index change after heat treatment.…”
Section: Figs 4-7 Show the Evolution Of Photo-induced Refractive Indmentioning
confidence: 99%
“…Sodium silicate glasses are known to luminesce under ultraviolet and x-ray irradiation in a wide range of temperatures with a maximum luminescence energy of 3.4 eV [7]. Trukhin et al [8] have measured the excitation spectra, the kinetics, and the degree of polarization of luminescence in high-purity sodium silicate glasses under excitation with ultraviolet light with photon energies exceeding 5.5 eV [see Fig. 1(a)].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the luminescence is caused by the intrinsic anisotropic structural motif in the glass, labeled L center, which is also responsible for the fundamental absorption edge of high-purity silicate glasses. This luminescence can be caused also by the decay of unstable color centers as a result of thermostimulated processes [7] or tunneling recombination of electron and hole centers [8,9].…”
Section: Introductionmentioning
confidence: 99%